Male Carriers of the FMR1 Premutation Show Altered Hippocampal-Prefrontal Function During Memory Encoding - Wang, John M.; Koldewyn, Kami; Hashimoto, Ryu-ichiro; Schneider, Andrea; Li, Lien; Tassone, Flora; Cheung, Katherine; Hagerman, Paul; Hessl, David; Rivera, Susan M. (Frontiers in Human Neuroscience, 2012)
Previous functional MRI (fMRI) studies have shown that fragile X mental retardation 1 (FMR1) premutation allele carriers (FXPCs) exhibit decreased hippocampal activation during a recall task and lower inferior frontal activation during a working memory task compared to matched controls. The molecular characteristics of FXPCs includes 55 to 200 CGG trinucleoutide expansions, increased FMR1 mRNA levels, and decreased FMRP levels especially at higher repeat sizes. In the current study, we utilized MRI to examine differences in hippocampal volume and function during an encoding task in young male FXPCs. While no decreases in either hippocampal volume or hippocampal activity were observed during the encoding task in FXPCs, FMRP level (measured in blood) correlated with decreases in parahippocampal activation. In addition, activity in the right dorsolateral prefrontal cortex during correctly encoded trials correlated negatively with mRNA levels. These results, as well as the established biological effects associated with elevated mRNA levels and decreased FMRP levels on dendritic maturation and axonal growth, prompted us to explore functional connectivity between the hippocampus, prefrontal cortex, and parahippocampal gyrus using a psychophysiological interaction analysis. In FXPCs, the right hippocampus evinced significantly lower connectivity with right ventrolateral prefrontal cortex (VLPFC) and right parahippocampal gyrus. Furthermore, the weaker connectivity between the right hippocampus and VLPFC was associated with reduced FMRP in the FXPC group. These results suggest that while FXPCs show relatively typical brain response during encoding, faulty connectivity between frontal and hippocampal regions may have subsequent effects on recall and working memory.